i-Mutawwif: A language traveller guide (Arabic-English-Malay) for pilgrims via mobile phones - Sahrir, Muhammad Sabri; Ismail, Taufik; Yahaya, Mohd Firdaus; Zubir, Muhamad Azhar; Nordin, Mohd. Shukri; Mohin, Mohaida (2018)
A poster presentation in Malaysia Technology Expo 2018, PWTC